Nitro-oleic acid triggers ROS production via NADPH oxidase activation in plants: A pharmacological approach - Arruebarrena Di Palma, Andrés (2020)
Nitrated fatty acids (NO2-FAs) are important signaling molecules in mammals. NO2-FAs are formed by the addition reaction of nitric oxide- and nitrite-derived nitrogen dioxide with unsaturated fatty acid double bonds. The study of NO2-FAs in plant systems constitutes an interesting and emerging area. The presence of NO2-FA has been reported in olives, peas, rice and Arabidopsis. To gain a better understanding of the role of NO2-FA on plant physiology, we analyzed the effects of exogenous application of nitro-oleic acid (NO2-OA). In tomato cell suspensions we found that NO2-OA induced reactive oxygen species (ROS) production in a dose-dependent manner via activation of NADPH oxidases, a mechanism that requires calcium entry from the extracellular compartment and protein kinase activation. In tomato and Arabidopsis leaves, NO2-OA treatments induced two waves of ROS production, resembling plant defense responses. Arabidopsis NADPH oxidase mutants showed that NADPH isoform D (RBOHD) was required for NO2-OA-induced ROS production. In addition, on Arabidopsis isolated epidermis, NO2-OA induced stomatal closure via RBOHD and F. Altogether, these results indicate that NO2-OA triggers NADPH oxidase activation revealing a new signaling role in plants.